BEYOND ANTHROPOCENTICISM: A DEEP ECOLOGICAL ANALYSIS OF KATE GRENVILLE’S SARAH THORNHILL - R. Kaveya; Vijaya, K. R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study examines Kate Grenville’s Sarah Thornhill through the framework of deep ecological theory, addressing anthropocentric perspectives and highlighting the novel’s promotion of a more interconnected and inclusive relationship between humans and the natural world.Using Val Plumwood’s critique of human-centred hierarchies, the study explores Grenville’s critique of the colonial mindset that elevates human dominance over nature, overlooking the inherent worth of non-human life.Through the narrative, Grenville portrays the interdependence of human and non-human life while critiquing the ecological and cultural consequences of anthropocentrism. Sarah Thornhill emerges as a profound exploration of the moral and ecological responsibilities of colonial societies, promoting a sustainable and inclusive worldview that honours the interconnectedness of all life forms.